Synthesis of L-Phenylalanine Ester Derivatives of p-tert-butylcalix[8]arene - Huang, S.J.; W. Yin, A.; Wu, C.B. (Asian Journal of Chemistry, 2011)
Synthetic routes were developed to link L-phenylalanine ester at the lower rim of p-tertbutylcalix[ 8]arene. Amide-type halides (2a-c) were synthesized by chloroacetic chloride and L-phenylalanine ester hydrochloride (1a-c), then reacted with p-tert-butylcalix[8]arene to produce L-phenylalanine ester derivatives of p-tert-butylcalix[8]arene (4a-c). The structure of the new compouds were characterized by IR and 1H NMR spectra.